The hearsay evidence and some of its exceptions / Abdul Aziz Mohamad - Mohamad, Abdul Aziz (Faculty of Law, 1985)
It is a general principal in the law of evidence that if any fact is to be proved against anymore, it ought to be proved in his presence by the testimony of a witness sworn to speak the truth; so that the person who is to be affected by the evidence has an opportunity of the witness as to his means of knowledge, and concerning his statement. In its legal sense "hearsay" evidence is all evidence which does not derive its value solely from the credit given to the witness himself, but which rest also in part, on the veracity and competance of some other person. Phipson defines it as an oral or written statements made by persons who are not parties and are not called as witnesses. These statements are inadmissible to prove the truth of the matter stated.